Gender prejudice speeches in media publications and their relationship with the image-building of former president of Brazil Dilma Rousseff - Alves Palacios, Rosiane (2021)
This study formulated an argument linking glass ceiling to Max Weber’s legitimacy of power based on newspaper reports about former President Dilma Rousseff. It aimed to analyze possible signs of gender bias in such reports, their connection with the former president’s image-building, and the possibility of legitimacy of power in her term of office. The selected method was narrative research with document and speech analysis. The association of theoretical issues provided elements to analyze the nuances of power when considering gender and the role of gender bias in media publications focused on sexism, which influenced the image-building of the former Brazilian president.